Fusobacterium nucleatum downregulated MLH1 expression in colorectal cancer by activating autophagy-lysosome pathway - Ding, Tingting; Wu, Minkang; Zhao, Li; Liu, Hu; Cao, Xuanke; Guo, Jing; Zhu, Xingchen; Zhao, Lamei; Zhang, Heping; Gao, Yaohui; Wei, Qing (Frontiers in Immunology, 2025)
BackgroundsFusobacterium nucleatum (F. nucleatum) has been shown to be associated with immunotherapy in colorectal cancer (CRC), but its exact mechanism needs to be further explored.MethodsWe first analyzed the correlation between F. nucleatum abundance and mismatch repair (MMR) protein deficiency in CRC tissues from 567 patients. We then treated CRC cells and tissues with F. nucleatum and its metabolites. RNA sequencing was used to evaluate the involved pathways, and non-targeted metabolomics was employed to analyze the metabolites regulating MLH1. CRC cells were treated with butyrate, a metabolite of F. nucleatum, with or without the autophagy-lysosome pathway inhibitor chloroquine or mTOR activator MHY1485. Finally, subcutaneous tumors of BALB/C mice were treated with PD-L1 blockade, butyrate, or their combination.ResultsThe results showed that the abundance of F. nucleatum in CRC tissues is correlated with MSI and MLH1 deficiency. F. nucleatum, its culture supernatant, and its metabolite butyrate cause the downregulation of MLH1 protein via autophagy-lysosome pathway. Subcutaneous tumors in mice received the combined treatment of PD-L1 blockade and butyrate shrink more evidently than those disposed by single therapy.ConclusionsF. nucleatum reduces MLH1 expression via the lysosomal pathway by butyrate, leading to deficient mismatch repair (dMMR), which may yield therapeutic benefits in CRC patients with microsatellite stability (MSS).